Pesantren sebagai Benteng Ideologi Pancasila (Studi di Kabupaten Rejang Lebong dan Kabupaten Kepahiang) - Arif Mustofa; Mabrur Syah (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Islamic boarding schools as educational institutions that have the principal principle of tafaaquh fi din have a tremendous influence on their santri. In addition, history also records from before the independent state of Indonesia, that pesantren became the frontline in expelling colonial colonizers and presenting peace in the archipelago even today. Even so, lately there have been a number of pesantren that have lost their way, they have stopped paying attention to the security and peace of the nation, they only think that in a pesantren it is a place to explore religious knowledge not others. Therefore, the purpose of this research is to explore the pesantren in fortifying the Pancasila. This study is a linear field with a descriptive qualitative approach, where data collected in the form of written or oral words from people who are the subject of research and observable behavior. Research data is sought through observation, interviews, and documentation. This research produces several things: first; the role of pesantren in rejang lebong and kepahiang districts is very good in terms of education, da'wah which is tasamuh, religious and moral services as well as ukhuwah islamiyah, except the second pesantren as Syafi'i imam; the efforts made by the pesantren in fortifying Pancasila, namely: the formation of friendly Islam with the TNI and the Police and the Commemoration of national and Islamic holidays, as well as social services. In contrast to the efforts made by the imam as Syafi'i pesantren which is to establish communication with the guardians of the santri who agree with them.